Fenestrated stent graft repair of abdominal aortic aneurysm: Hemodynamic analysis of the effect of fenestrated stents on the renal arteries - Sun, Zhonghua; Chaichana, Thanapong (My University, 2010)
Objective: We wanted to investigate the hemodynamic effect of fenestrated stents on the renal arteries with using a fluid structure interaction method. Materials and Methods: Two representative patients who each had abdominal aortic aneurysm that was treated with fenestrated stent grafts were selected for the study. 3D realistic aorta models for the main artery branches and aneurysm were generated based on the multislice CT scans from two patients with different aortic geometries. The simulated fenestrated stents were designed and modelled based on the 3D intraluminal appearance, and these were placed inside the renal artery with an intra-aortic protrusion of 5.0-7.0 mm to reflect the actual patients' treatment. The stent wire thickness was simulated with a diameter of 0.4 mm and hemodynamic analysis was performed at different cardiac cycles. Results: Our results showed that the effect of the fenestrated stent wires on the renal blood flow was minimal because the flow velocity was not significantly affected when compared to that calculated at pre-stent graft implantation, and this was despite the presence of recirculation patterns at the proximal part of the renal arteries. The wall pressure was found to be significantly decreased after fenestration, yet no significant change of the wall shear stress was noticed at post-fenestration, although the wall shear stress was shown to decrease slightly at the proximal aneurysm necks. Conclusion: Our analysis demonstrates that the hemodynamic effect of fenestrated renal stents on the renal arteries is insignificant. Further studies are needed to investigate the effect of different lengths of stent protrusion with variable stent thicknesses on the renal blood flow, and this is valuable for understanding the long-term outcomes of fenestrated repair.
Keywords: Abdominal aortic aneurysm; Fenestration, renal artery; Flow analysis; Stent graft